The muscle morphology of elite sprint running - Miller, R.; Balshaw, T. G.; Massey, G. J.; Maeo, S.; Lanza, M. B.; Johnston, M.; Allen, S. J.; Folland, J. P. (Medicine & Science in Sports & Exercise, 2021)
The influence of muscle morphology and strength characteristics on sprint running performance, especially at elite level, is unclear. Purpose: This study aimed to investigate the differences in muscle volumes and strength between male elite sprinters, sub-elite sprinters, and untrained controls and to assess the relationships of muscle volumes and strength with sprint performance. Methods:Five elite sprinters (100-m season`s best equivalent [SBE100], 10.10 ± 0.07 s), 26 sub-elite sprinters (SBE100, 10.80 ± 0.30 s), and 11 untrained control participants underwent 1) 3-T magnetic resonance imaging scans to determine the volume of 23 individual lower limb muscles/compartments and 5 functional muscle groups and 2) isometric strength assessment of lower body muscle groups. Results: Total lower body muscularity was distinct between the groups (controls < sub-elite +20% < elite +48%). The hip extensors exhibited the largest muscle group differences/relationships (elite, +32% absolute and +15% relative [per kg] volume, vs sub-elite explaining 31%-48% of the variability in SBE100), whereas the plantarflexors showed no differences between sprint groups. Individual muscle differences showed pronounced anatomical specificity (elite vs sub-elite absolute volume range, +57% to -9%). Three hip muscles were consistently larger in elite vs sub-elite (tensor fasciae latae, sartorius, and gluteus maximus; absolute, +45%-57%; relative volume, +25%-37%), and gluteus maximus volume alone explained 34%-44% of the variance in SBE100. The isometric strength of several muscle groups was greater in both sprint groups than controls but similar for the sprint groups and not related to SBE100. Conclusions: These findings demonstrate the pronounced inhomogeneity and anatomically specific muscularity required for fast sprinting and provides novel, robust evidence that greater hip extensor and gluteus maximus volumes discriminate between elite and sub-elite sprinters and are strongly associated with sprinting performance.